2014
DOI: 10.3390/molecules190914699
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanisms Involved in Antinociception Produced by the Alkaloid Caulerpine

Abstract: Abstract:In previous works we showed that oral administration of caulerpine, a bisindole alkaloid isolated from algae of the genus Caulerpa, produced antinociception when assessed in chemical and thermal models of nociception. In this study, we evaluated the possible OPEN ACCESSMolecules 2014, 19 14700 mechanism of action of this alkaloid in mice, using the writhing test. The antinociceptive effect of caulerpine was not affected by intraperitoneal (i.p.) pretreatment of mice with naloxone, flumazenil, L-argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The new compounds were the racemosines A-C 678-680, 448,449 bisindole alkaloids isolated from Caulerpa racemosa which are biosynthetically related to the well-established green algal metabolite caulerpin, also from a Caulerpa sp. 450 Caulerpin featured in studies of antinociception mechanisms 451 and the antituberculosis activities of caulerpin and synthetic analogues. 452 Included in the green algal literature for 2014 was a study on the effect of natural lycopene (E/Z mixture) on a human prostate cancer cell line, 453 while a thought-provoking paper tackled a problem all marine natural product chemists should be alert tothe misuse of taxonomic descriptors and the implications that this has.…”
Section: Green Algaementioning
confidence: 99%
“…The new compounds were the racemosines A-C 678-680, 448,449 bisindole alkaloids isolated from Caulerpa racemosa which are biosynthetically related to the well-established green algal metabolite caulerpin, also from a Caulerpa sp. 450 Caulerpin featured in studies of antinociception mechanisms 451 and the antituberculosis activities of caulerpin and synthetic analogues. 452 Included in the green algal literature for 2014 was a study on the effect of natural lycopene (E/Z mixture) on a human prostate cancer cell line, 453 while a thought-provoking paper tackled a problem all marine natural product chemists should be alert tothe misuse of taxonomic descriptors and the implications that this has.…”
Section: Green Algaementioning
confidence: 99%
“…Two studies reported marine compounds (198,200) that contributed to nociceptive pharmacology. Cavalcante-Silva and colleagues assessed the mechanism involved in in vivo antinociception produced by the bisindole alkaloid caulerpine (198), isolated from the marine alga Caulerpa, demonstrating that, in the in vivo murine writhing test, the effect was likely mediated by "pathways involving α2-adrenoceptors and 5-HT3 receptors", thus proposing cualerpine as a possible "dual-action analgesic drug(s)" [214]. Chen and colleagues investigated the anti-neuropathic properties of the antimicrobial peptide piscidin (200) and observed that the compound demonstrated in vivo anti-nociceptive effects in a rat model of neuropathy by a signaling mechanism that suppressed up-regulation of interleukin-1 in microglia and phosphorylated mammalian target of rapamycin in astrocytes, concluding it "may have potential for development as an alternative pain-alleviating agent" [216].…”
Section: Marine Compounds Affecting the Nervous Systemmentioning
confidence: 99%
“…Caulerpin ( 1 ) ( Figure ) is a bis‐indole alkaloid, isolated mostly from algae of genus Caulerpa and some from red algae, it displayed several biological activities such as anti‐inflammatory, antinociceptive, antiviral, anti‐herpes, and anti‐tuberculosis, meanwhile lack of toxicity for it was found in mouse study . Additionally, caulerpin ( 1 ) was also found to be a chemical agent as a plant growth promoter and regulator, as well as a rust inhibitor in mild steel .…”
Section: Figurementioning
confidence: 99%